Does the Intensity of Gadget Use Impact Social and Emotional Development of Children aged 48-72 Months? - Rukmana, Nabila Ilma Nisa; Ainy Fardana, Nur; Dewanti, Linda; Mujtaba, Farah (Al-Athfal: Jurnal Pendidikan Anak, 2021)
Purpose –This study aims to analyze the correlation between the intensity of gadget use and the social-emotional development of children aged 48-72 months.Design/methods/approach – The Study uses quantitative research with a cross-sectional study. The sample includes 126 children using a simple random sampling technique at Al-Furqon Kindergarten and Bunda Ghifari Kindergarten Surabaya, Indonesia. The independent variable is the intensity of gadget use which is measured using a questionnaire. The dependent variable is the children’s social-emotional development as measured by the Questionnaire of Problems and Emotional Behavior.Findings – There is a significant correlation between the intensity of gadget usage and the social-emotional development of children aged 48-72 months (p-value < 0.05). High-intensity gadget use will increase their social-emotional development in the referral category, which means it requires treatment by the experts.Research implications/limitations - The result of this study supports the theory that high intensity of gadget usage on children will affect their social and emotional development. This study only focuses on children’s social and emotional development without examining another developmental variable that may affect the study results.Practical implications – Parents are expected to play a role in supervising and limiting the use of gadgets on children to avoid the negative impacts.Originality/value –This study contributes to the literature by showing the effect of gadget use on children’s social and emotional development. Paper type Research paper